2018
DOI: 10.1002/cnm.2968
|View full text |Cite
|
Sign up to set email alerts
|

Regional deposition of nasal sprays in adults: A wide ranging computational study

Abstract: The present work examines regional deposition within the nose for nasal sprays over a large and wide ranging parameter space by using numerical simulation. A set of 7 realistic adult nasal airway geometries was defined based on computed tomography images. Deposition in 6 regions of each nasal airway geometry (the vestibule, valve, anterior turbinate, posterior turbinate, olfactory, and nasopharynx) was determined for varying particle diameter, spray cone angle, spray release direction, particle injection speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Flow physics undergo a transition over this range; e.g. the 15 L/min flow through anatomically realistic nasal conduits lies in the laminar regime, [17][18][19][20][21][22][23][24][25][26][27][28] the flow structures however devolve into turbulence [29][30][31][32] at higher inhalation rates. Numerical schemes, that are used in this study to track respiratory transport, have been selected accordingly (see the supplementary methods section).…”
Section: /8mentioning
confidence: 99%
See 1 more Smart Citation
“…Flow physics undergo a transition over this range; e.g. the 15 L/min flow through anatomically realistic nasal conduits lies in the laminar regime, [17][18][19][20][21][22][23][24][25][26][27][28] the flow structures however devolve into turbulence [29][30][31][32] at higher inhalation rates. Numerical schemes, that are used in this study to track respiratory transport, have been selected accordingly (see the supplementary methods section).…”
Section: /8mentioning
confidence: 99%
“…15 L/min) corresponds to comfortable resting breathing, with the viscous-laminar steady-state flow physics model standing in as a close approximation. [17][18][19][20][21][22][23][24][25][26][27][28] At higher flow rates (extreme values of which may sometimes lead to nasal valve collapse), the shear layer separation from the tortuous walls of the anatomic geometries results in turbulence. [29][30][31][32] While accounting for the turbulent characteristics of the ambient airflow, the study averages the droplet deposition percentages from implementation of two distinct categories of numerical schemes, viz.…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…Other computational studies include: Keeler et al [17] who investigated the influence of nasal airway geometry from different ethnic groups on spray particle deposition and found that white and Latin Americans had the least patent nasal cavity, although this was based on four models per ethnic group; Kiaee et al [18] that found particle diameter and particle injection speed, were the dominant parameters (other parameters were spray cone angle, spray release direction, and particle injection location) that influenced deposition in seven adult nasal airways; and Fung et al [19] performed CFD modelling to characterise the nasal spray atomization stage. Djupesland et al [20] showed a bi-directional nasal delivery concept reduced lung deposition by taking advantage of the posterior connection between the nasal passages persisting when the soft palate automatically closes during oral exhalation.…”
Section: Introductionmentioning
confidence: 99%
“…However, many computational studies with drug delivery have only applied a steady flow condition. For example studies have used laminar steady inspiratory flow rates [3, 4, 17, 18] when the flow rate was approximately <15L/minor, and steady RANS (Reynolds Averaged Navier-Stokes) turbulent flows when the flow rate was >20L/min [16, 21]. While there are many ways to inhale during drug delivery, this study looked at the influence of a sniff compared to commonly used steady flow rate, and a zero inhalation flow on particle deposition in the human nasal cavity.…”
Section: Introductionmentioning
confidence: 99%
“…Allometric relations 11 show that the minute inhalation is approximately 14.5 -20.0 L/min for a 65-kg male and 8.8 -22.4 L/min for a 65-kg female, both for gentle steady breathing. For simplicity, in this study, we have simulated inhalation at only 15 L/min; the process can be modeled using viscous-laminar steady state flow physics schemes [12][13][14][15][16][17][18][19][20][21] .…”
Section: Development Of Anatomically Realistic Computational Fluid Mechanics Modelsmentioning
confidence: 99%